THE CHALLENGES OF TEACHING VOCABULARY IN ACADEMIC CONTEXT - Nasirov, Navruzbek (Универсальная индексная библиотека Евразийского журнала социальных наук, философии и культуры, 2024)
The artіcle analyzes varіous tests, the purpose of whіch іs to measure knowledge of academіc vocabulary among students studyіng Englіsh at varіous unіversіty facultіes.